FEATURES OF THE INNOVATIVE FORMS OF INTEGRATION FOR THE ENTREPRENEURIAL UNIVERSITIES - Mytsiuk, S. (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2019)
The article substantiates the necessity and determination of the prospects for the innovative development of intellectual resources in the conditions of the formation of entrepreneurial-type universities in Ukraine. The process of transformation of the role of intellectual capital in the modern economy is analyzed, the evolution of approaches to the development of universities is studied, the specifics of the formation of entrepreneurial-type universities are defined, and intellectual resources are designated as a factor in the development of modern universities. The possibility of creating a fundamentally integrated integrated structure of a priority technological platform, including a HEI, research institutions and enterprises, an innovative integrated structure, has been determined. Also considered are important innovative forms of integration of science, business and education – clusters and public-private partnerships. The role of the state in supporting the development of interaction between enterprises and scientific and educational organizations has been determined. The article examines the global trends in the development of universities: general patterns and national characteristics, analyzes patterns and prerequisites for the formation of entrepreneurial-type universities in Ukraine, and defines the values of intellectual resources in the formation of entrepreneurial-type universities. The article considers the innovative development of intellectual resources in the context of the formation of entrepreneurial-type universities, identifies promising areas for enhancing the innovative development of intellectual resources. The algorithm for introducing the competence approach to the process of innovative development of intellectual resources for the formation and development of business-type universities in Ukraine is analyzed.Keywords: entrepreneurial university, innovation, intellectual capital, knowledge transfer, clusters. References1. Clark B. R. (2008). Creating Entrepreneurial Universities: Organizational Pathways of Transformation. Iau Press. Issues In Higher Education. Wagon Lane, Bingley BD16 1WA. UK: Emerald Group Publishing Limited. Howard House, 164 p.2. Etzkowitz H. (2002). Incubation of incubators: innovation as a triple helix of university-industry – government networks. Science and Public Policy, 29(2): 115–128.3. Etzkowitz H., Chunyan Zhou (2007). Regional Innovation Initiator: The Entrepreneurial University in Various Triple Helix Models. The paper for Triple Helix VI conference, Singspore, May 16–18.4. Etzkowizt H., Goktepe-Hulten D. (2010). Maybe they can? University technology transfer offices as regional growth engines. Int. J. Technology Transfer and Commercialisation, 9(1/2): 166–181.5. Etzkowitz H., Klofsten M. (2005). The Innovating Region: Towards a Theory of Knowledge Based Regional Development. Research Management, 35(3): 243–255.6. Etzkowitz H., Loe L. (2000). The Dynamics of Innovation: From National System and «Mode 2» to a Triple Helix of University-Industry-Government Relations. Research Policy, 29: 109–123.7. Etzkowitz H., Webster A., Gebhardt C., Terra B.R.C. (2000). The future of the university and the university of the future: evoluation of ivory tower to entrepreneurial paradigm. Research Policy, 29: 313–330.8. Etzkowitz H. (2008). The Triple Helix: University-IndustryGovernment Innovation In Action. London: Routledge, 2008. 177 p.9. North K. The anatomy of European knowledge regions: a comparative analysis. Forth world conference on intellectual capital for communities. Paris, May 2008. <http//www.web.worldbank.org>10. Röpke J. The Entrepreneurial University, Innovation, academic knowledge creation and regional development in a globalized economy. Working Paper Department of Economics,Philipps-Universität Marburg, Germany, 5.1.2000. p. 3 .<http://etc.online.unimarburg.de/LinkedDocuments/mafex_rj_entreuni.pdf>.11. Грищенко І. М. (2015). Теоретико-методологічне обгрунтування ефективних фінансово-економічних моделей розвитку вищої школи [Theoretical and methodological substantiation of effective financial and economic models of higher education development]. Монографія (рукопис); за заг. ред. чл.-кор. НАПН України, д-ра екон. наук., проф. І. М. Грищенка. К., 2015. 236 с.12. Згуровський М. З. (2011) Дослідницькі університети як центри інноваційного розвитку країни [Research universities as centers of innovative development of the country]. Дзеркало тижня. 22-28 січня 2011 р. № 2. С. 1-13.13. Корольова Т. С. (2009) Складові інноваційної системи вищих навчальних закладів [The Components of the innovational system of higher education institutions] Культура народів Причорномор'я. Секція: Економіка. Сімферополь: Міжуніверситетський центр «Крим», 2009. № 171. С. 42–45.14. Луговий В. І. (2012) Економічно-організаційні засади освіти в Україні та світі: порівняльний аналіз [Economic and organizational principles of education in Ukraine and the world: a comparative analysis]. Педагогіка і психологія. 2012, № 1. С. 64-70.15. Мірзодаєва Т. В., Романовський О. О. (2012) Концептуальні підходи до формування міждержавних інноваційно-освітніх мереж підприємницького типу [Conceptual approaches to the formation of interstate business-type innovation-educational networks]. Міжнародний науковий вісник. Ужгород: Зак ДУ. 2012. Вип.5(24). С. 328.16. Романовський О. О. (2012) Феномен підприємництва в університетах світу: монографія [The phenomenon of entrepreneurship in universities in the world: a monograph]. Вінниця: Нова Книга. 2012. 504 с.17. Романовський О. О. Розвиток академічного підприємництва і підприємницьких вищих навчальних закладів в умовах глобалізації [Development of academic entrepreneurship and entrepreneurial higher education institutions in the context of globalization]. <http://www.economy.nayka.com.ua/pdf/11_2015/16.pdf>18. Смоланка В. І., Артьомов І. В. Інноваційна діяльність університетів України: аналітичний огляд: передмова [Innovation activity of Ukrainian universities: analytical review: preface]. Інформаційний бюлетень наукового проекту «Інноваційний університет – інструмент інтеграції в європейський освітній і науковий простір». Ужгород. 2015. Випуск 1, <https://www.uzhnu.edu.ua/uk/infocentre/get/9718>19. Харин А. А. (2012) Методология формирования инновационных интегрированных структур образования, науки и бизнеса: диссертация на соискание степени доктора экономических наук: по специальности 08.00.05 [Methodology of formation of innovative integrated structures of education, science and business: the dissertation for the degree of Doctor of Economic Sciences: in the specialty 08.00.05]. ГОУВПО «Государственный университет управления». М., 2012. 304 с.20. Інноваційні дослідницькі університети як чинник модернізації освітньо-наукової сфери та розбудови суспільства знань. Аналітична записка [Innovative research universities as a factor in modernizing the educational and scientific sphere and building a knowledge society], http://www.niss.gov.ua/articles/1427/.

В статье обоснована необходимость и определение перспектив инновационного развития интеллектуальных ресурсов в условиях формирования университетов предпринимательского типа в Украине. Проанализирован процесс трансформации роли интеллектуального капитала в условиях современной экономики, исследована эволюция подходов к развитию университетов, определена специфика формирования университетов предпринимательского типа, а интеллектуальные ресурсы обозначены как фактор развития современных университетов. Определена возможность создания принципиально новой интегрированной структуры приоритетной технологической платформы, включающей ВУЗы, научно-исследовательские учреждения и предприятия – инновационная интегрированная структура. Рассмотрены также важные инновационные формы интеграции науки, бизнеса и образования – кластеры и государственно-частные партнерства. Определена роль государства в поддержке развития взаимодействия предприятий и научно-образовательных организаций. В статье исследованы глобальные тенденции развития университетов: общие закономерности и национальные особенности, проанализированы закономерности и предпосылки формирования университетов предпринимательского типа в Украине, определены значения интеллектуальных ресурсов в формировании университетов предпринимательского типа. В статье рассмотрено инновационное развитие интеллектуальных ресурсов в условиях формирования университетов предпринимательского типа, определены перспективные направления активизации инновационного развития интеллектуальных ресурсов. Проанализирован алгоритм внедрения компетентностного подхода в процесс инновационного развития интеллектуальных ресурсов для формирования и развития университетов предпринимательского типа в Украине.Ключевые слова: предпринимательский университет, инновации, интеллектуальный капитал, трансфер знаний, кластеры.

В статті обґрунтовано необхідність та визначення перспектив інноваційного розвитку інтелектуальних ресурсів в умовах формування університетів підприємницького типу в Україні. Проаналізовано процес трансформації ролі інтелектуального капіталу в умовах сучасної економіки, досліджено еволюцію підходів до розвитку університетів, визначено специфіку формування університетів підприємницького типу, інтелектуальні ресурси позначені як фактор розвитку сучасних університетів.Actual problems of international relations. Release 140. 201982Визначено можливість створення принципово нової інтегрованої структури пріоритетної технологічної платформи, що включає ЗВО, науково-дослідні установи і підприємства – інноваційна інтегрована структура. Розглянуто також важливі інноваційні форми інтеграції науки, бізнесу і освіти – кластери та державно-приватні партнерства. Визначено роль держави в підтримці розвитку взаємодії підприємств і науково-освітніх організацій. В статті досліджені глобальні тенденції розвитку університетів: загальні закономірності і національні особливості, проаналізовано закономірності та передумови формування університетів підприємницького типу в Україні, визначено значення інтелектуальних ресурсів у формуванні університетів підприємницького типу. В статті розглянуто інноваційний розвиток інтелектуальних ресурсів в умовах формування університетів підприємницького типу, визначені перспективні напрями активізації інноваційного розвитку інтелектуальних ресурсів. Проаналізовано алгоритм впровадження компетентнісного підходу в процес інноваційного розвитку інтелектуальних ресурсів для формування і розвитку університетів підприємницького типу в Україні.Ключові слова: підприємницькій університет, інновації, інтелектуальний капітал, трансфер знань, кластери.
ОСОБЕННОСТИ ИННОВАЦИОННЫХ ФОРМ ИНТЕГРАЦИИ ПРЕДПРИНИМАТЕЛЬСКИХ УНИВЕРСИТЕТОВ
ОСОБЛИВОСТІ ІННОВАЦІЙНИХ ФОРМ ІНТЕГРАЦІЇ ПІДПРИЄМНИЦЬКИХ УНІВЕРСИТЕТІВ